Peningkatan Hasil Belajar Ilmu Pengetahuan Alam pada Siswa dengan Menggunakan Model Pembelajaran Think Pair and Share - Mashudi Alamsyah; Yulistiana Yulistiana (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
The purpose of this study is to determine the increase of science learning outcomes in grade VII students using the model of learning Think Pair and Share at SMPN 241 Jakarta. The research method used is the experimental method, by taking the number of samples each group of 30 students, taken by using simple random sampling technique. The instrument used is a test instrument in the form of multiple choice of 27 questions. Test data analysis requirements performed is the normality test (using the chi-square test) and homogeneity test (using the F-test). Based on the test results of normality experimental data obtained X²hit = 2,517; control class data obtained X²hit = 1,611; where X²hit <X²tab and the result is normally distributed. Homogeneity test obtained by value of both group equal to 1,103 with Fhit <Ftab, and result of data of both group is homogeneous. Based on the result of t-test calculation, the value of tcount 23,04 with dk58 (using linear interpolation) resulted in ttable 1,942. Thus, with thitung> ttabel result H1 accepted and H0 rejected. Thus, there is a significant improvement between the Think Pair and Share learning model of the learning outcome of the IPA.